2003
DOI: 10.1113/jphysiol.2003.051680
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Mobilisation and CCK Secretion Induced by Modified Fatty Acids and Latex Microspheres Reveal Dual Receptor Mechanisms for Lipid Stimulation of STC‐1 Cells

Abstract: How fatty acids stimulate enteroendocrine cells to release cholecystokinin (CCK) is largely unknown. Recently, we proposed that the murine enteroendocrine cell line, STC‐1, responds to insoluble fatty acid aggregates rather than fatty acid monomers in solution. This hypothesis led to two testable predictions. First, other insoluble particles of similar size but unrelated to fatty acid may be able to stimulate STC‐1 cells in a similar fashion to dodecanoic acid and second, fatty acid sensing in STC‐1 cells shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Accordingly, STC-1 cells stimulated by fatty acids exhibit an increase in CCK production (24). Analysis of CCK production by STC-1 cells stimulated in vitro with the TLR agonists LPS, flagellin, and CpG-ODN revealed a progressive increase in CCK levels with dose-dependent responses for each agonist, going to plateau after 18 h of treatment (Fig.…”
Section: Stc-1 Cells Activated By Tlr4 Agonist Lps Tlr5 Agonist Flagmentioning
confidence: 99%
“…Accordingly, STC-1 cells stimulated by fatty acids exhibit an increase in CCK production (24). Analysis of CCK production by STC-1 cells stimulated in vitro with the TLR agonists LPS, flagellin, and CpG-ODN revealed a progressive increase in CCK levels with dose-dependent responses for each agonist, going to plateau after 18 h of treatment (Fig.…”
Section: Stc-1 Cells Activated By Tlr4 Agonist Lps Tlr5 Agonist Flagmentioning
confidence: 99%
“…This evidence was based upon an elaborate series of experiments using microfilters and sonication to remove or disrupt particulate FA aggregates, and led to the suggestion that both STC-1 cells and an additional EEC line (GluTAg) were responding directly to the aggregates rather than to monomeric fatty acids in solution. Further evidence was sought to test this hypothesis by attempting to mimic the physical nature of FA aggregates with non-lipid particles of similar size (Kazmi et al, 2003). These experiments demonstrated that certain latex particles (LP) could indeed generate intracellular [Ca 2þ ] i transients and induce CCK release from STC-1 cells, in a manner seemingly comparable to fatty acids.…”
Section: Introductionmentioning
confidence: 98%
“…The time elapsed after sonication affects solubility, and re-aggregation of fatty acid occurs, which in turn affects the cellular responses to C 12 (10). This has led to the suggestion that fatty acid effects may in part be exerted by the extracellular aggregates themselves (10,11). Removing Ca 2ϩ from the buffer renders C 12 far more soluble and stable in its physicochemical state, yet results in [Ca 2ϩ ] i responses that are rapid, reversible, and more reproducible than in the presence of extracellular Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent data have demonstrated that STC-1 cells are indeed able to respond to such unsolubilized particulate material, either lipid or nonlipid in origin, and this may underpin a component of the fatty acid response (10,11). However, this cannot be the sole mechanism because, under different physicochemical conditions (e.g.…”
mentioning
confidence: 99%